Gender inequalities in the health of immigrants and workplace discrimination in Czechia - Dzúrová, Dagmar; Drbohlav, Dušan (BioMed research international, 2014)
This study analyses the relationship between immigrants' self-reported/rated health (SRH) and their perceived working conditions in Czechia materialized via discrimination, based on the example of Ukrainian immigrants analyzed by gender dimension. The role of age, education, and marital status is also analyzed. A sample of native-born Czechs serves as a reference frame. A cross-sectional design was applied. Using data from two surveys of Ukrainian immigrants in Czechia and a countrywide health interview survey for Czechs, we analyse inequalities in SRH and workplace discrimination loads. Four binary logistic regression models were computed separately for women and men from Ukraine and Czechia to identify the determinants of fair/poor SRH. We found that only Ukrainian immigrant females were heavily exposed to all four measured types of workplace discrimination, thereby modifying and worsening the quality of their SRH. Determinants which are behind respondents' SRH differ between Ukrainian immigrants vis-à-vis Czechs with one exception. The "oldest age group" (41-62) contributes to poorer assessment of SRH among Ukrainian females, Czech females, and Czech males too. The lowest educational level (primary education) correlates with poor SRH within the sample of Czech males.
Keywords: Socioeconomic Factors; Cross-Sectional Studies; xenofobie; Workplace; Male; Xenophobia; Česká republika; Adult; Age Factors; socioekonomické faktory; dospělí; mužské pohlaví; Emigrants and Immigrants; Czech Republic; Sexism; lidé; ženské pohlaví; Humans; emigranti a imigranti; průřezové studie; věkové faktory; Female; lidé středního věku; pracoviště; sexismus; Middle Aged